Developing the Family Involvement Questionnaire-Long-Term Care: A Measure of Familial Involvement in the Lives of Residents at Long-Term Care Facilities. (3rd January 2018) - Fast, Christopher T; Houlihan, Daniel; Buchanan, Jeffrey A
Abstract: Introduction: Existing measures designed to assess family involvement in the lives of older adults residing in long-term care facilities are basic, using visitation frequency as the prominent gauge of involvement in a situation specific fashion. The purpose of this study was to design and validate a measure of family involvement that could be used to gauge more aspects of family involvement than visitation alone and be useful in a variety of settings for both researchers and long-term care facility administrators. Methods: Long-term facility staff were asked to assist in creating a 40-item questionnaire that used 4-point Likert scales to measure various aspects of family involvement. The finalized Family Involvement Questionnaire-Long-Term Care (FIQ-LTC) was distributed to the family members of older adults residing in long-term care facilities around the country. Results: A total of 410 participants responded. Researchers found that the FIQ-LTC was highly reliable (α = .965). Results also indicated that a significant correlation between distance and overall involvement ( r = −.121, p = .015) was no longer significant ( r = .17, p = .740) when the effect of a question asking the frequency of visitation was controlled for. Discussion: These results indicate that existing measures that use visitation frequency as the sole measure of involvement are insufficient. The newly developed FIQ-LTC can serve as a more complete measure of family involvement.